RAHASIA PENGULANGAN (REPITISI) AYAT DALAM SURAH AR-RAHMAN: Kajian Kitab Tafsir Ruh al-ma’ani Karya Al-Alusi - Muhammad Yunus; Uswatun Hasanah (Al Irfani: Journal of Al Qur'anic and Tafsir, 2020)
This article discusses the secret of the repetition of verses in surah ar-Rahman. On the one side, the repetition of the verse is one of the styles of language and kemu'jizatan al-Qur'an. However, on the other, both Muslims and orientalists are still debatable about the meaning of repetition (tiqrar) in the Koran. One of the things that discusses the secret meaning behind the repetition of verses is al-Alusi in the interpretation of Ruh al-Ma'ani. This research is literature, so the authors use a descriptive-analysis approach. Describe in general the Ruhal-Ma'ani tafsir and to do the analysis with writings in the form of journals or other scientific works. As a result, the secret behind the repetition of verses in the Qur'an according to al-Alusi is to determine the meaning of the previous verse, not as tauqid. As it is known in the science of balaghah that one of the methods of tauqid is by repeating the lafadz or verse, if more than three times it is not called tauqid (recitation), but the determination of meaning (taqrir al-ma'na) from befor